Osteopontin drives retinal ganglion cell resiliency in glaucomatous optic neuropathy - Zhao, Mengya; Toma, Kenichi; Kinde, Benyam; Li, Liang; Patel, Amit K.; Wu, Kong-Yan; Lum, Matthew R.; Tan, Chengxi; Hooper, Jody E.; Kriegstein, Arnold R.; La Torre, Anna; Liao, Yaping Joyce; et al. (Cell reports (Cambridge), 2023)
Chronic neurodegeneration and acute injuries lead to neuron losses via diverse processes. We compared retinal ganglion cell (RGC) responses between chronic glaucomatous conditions and the acute injury model. Among major RGC subclasses, αRGCs and intrinsically photosensitive RGCs (ipRGCs) preferentially survive glaucomatous conditions, similar to findings in the retina subject to axotomy. Focusing on an αRGC intrinsic factor, Osteopontin (secreted phosphoprotein 1 [Spp1]), we found an ectopic neuronal expression of Osteopontin (Spp1) in other RGCs subject to glaucomatous conditions. This contrasted with the Spp1 downregulation subject to axotomy. αRGC-specific Spp1 elimination led to significant αRGC loss, diminishing their resiliency. Spp1 overexpression led to robust neuroprotection of susceptible RGC subclasses under glaucomatous conditions. In contrast, Spp1 overexpression did not significantly protect RGCs subject to axotomy. Additionally, SPP1 marked adult human RGC subsets with large somata and SPP1 expression in the aqueous humor correlated with glaucoma severity. Our study reveals Spp1’s role in mediating neuronal resiliency in glaucoma. [Display omitted] •αRGCs and ipRGCs are resilient retinal neuron types in glaucomatous and axotomy conditions•Elevated and ectopic Spp1 expression among RGCs occurs in the glaucoma model, not axotomy•Neuronal Spp1 drives RGC neuroprotection in glaucomatous conditions but not in axotomy•SPP1 protein levels in aqueous humor correlate with glaucoma progression in patients Zhao et al. reported that retinal neuron subpopulations are resilient with ectopic Spp1 expression, subject to an experimental glaucomatous model with ocular hypertension. Spp1 overexpression renders other susceptible retinal neurons with neuroprotection subject to glaucomatous conditions. Elevated SPP1 levels in aqueous humor may be biomarkers for human glaucoma progression.